Resistance to adverse conditions and characterization of Cladosporium species from marine and terrestrial Antarctic samples - Simonetti, Flávio L. [UNESP]; Cabral, Lucélia [UNESP]; Chávez, Renato; Sette, Lara D. [UNESP] (My University, 2024)
Microbial adaptations to extreme environments can lead to biotechnological applications. This study aimed to evaluate the resistance of Antarctic Cladosporium to adverse conditions (temperature, salinity, UV radiation, and nutrients) and refine their taxonomy. Sequencing and phylogenetic analysis using ITS-act markers resulted in a more accurate taxonomic identification, revealing the presence of five different species, belonging to the complexes C. cladosporioides and C. sphaerospermum. The growth at different temperatures indicates that the soil isolates LAMAI 564 and 1800 (phylogenetically closely related) and LAMAI 2541 are psychrophilic, while the other isolates are psychrotolerant. The fungi isolated from the saline samples LAMAI 595, 616, and 1369 showed better growth results at higher salinity (15%). The fungi most resistant to UV radiation were isolated from terrestrial and marine samples (LAMAI 595, 616, 1800, and 564). LAMAI 595 and 616 (phylogenetically closely related and isolated from the same kind of sample) showed the capacity of nutritional versatility, growing well in both rich and poor-nutrient media. The fungus LAMAI 595 was the most promising for biotechnological application, exceeding the other isolates in the harsh conditions studied. The resistance of the Antarctic Cladosporium to adverse conditions opens new perspectives in the field of applied microbiology of extremophiles.
Keywords: biomolecules; biotechnology; extremophile; taxonomy